Electrolyte Engineering for Oxygen Evolution Reaction Over Non‐Noble Metal Electrodes Achieving High Current Density in the Presence of Chloride Ion. Issue 19 (1st September 2022) - Komiya, Hiroki; Shinagawa, Tatsuya; Takanabe, Kazuhiro
Abstract: Direct seawater electrolysis potentially simplifies the electrolysis process and leads to a decrease in the cost of green hydrogen production. However, impurities present in the seawater, especially chloride ions (Cl − ), cause corrosion of the electrode material, and its oxidation competes with the anodic oxygen evolution reaction (OER). By carefully tuning electrode substrate and electrolyte solutions, the CoFeO x H y /Ti electrode with high double‐layer capacitance actively and stably electro‐catalyzed the OER in potassium borate solutions at pH 9.2 in the presence of 0.5 mol kg −1 Cl − . The electrode possesses an active site motif composed of either a Co‐ or Fe‐domain and benefits from an enlarged surface area. Selective OER was demonstrated in Cl − ‐containing electrolyte solutions at an elevated reaction temperature, stably achieving 500 mA cm −2 at a mere potential of 1.67 V vs. reversible hydrogen electrode (RHE) at 353 K for multiple on‐off and long‐term testing processes with a faradaic efficiency of unity toward the OER. Abstract : Mind the gap : The thermodynamic potential gap between chloride oxidation and oxygen evolution reaction (OER) as shown in the blue area allows the CoFeO x H y electrocatalyst to produce O2 with near 100 % faradaic efficiency toward the OER even in the presence of chloride ions at any temperature.